UPAYA PENINGKATAN PEMBENTUKAN KARAKTER MELALUI PENERAPAN KURIKULUM MUATAN LOKAL TERHADAP PENGETAHUAN KEWIRAUSAHAN SISWA SMA NEGERI 7 DENPASAR - Cokorde Istri Mirah Kusuma Widiawati (Widyadari : Jurnal Pendidikan, 2020)
The purpose of this study is to determine whether the application of local content curriculum can improve the formation of character education and student responses to student entrepreneurial knowledge. This research is a school action research that was designed through action research in practical learning activities in schools. The design of this study was used as a measure of the success of the method applied. This school action research was conducted at SMA Negeri 7 Denpasar. Subjects in the study of class XI students of SMA Negeri 7 Denpasar in the odd semester of the 2019/2020 school year, and the object of research was the application of a local content curriculum in the formation of character education towards student entrepreneurship. This action research consists of four main activities, namely: (a) planning, (b) action, (c) observation, and (d) evaluation and reflection. The results showed that the application of local content curriculum can improve the ability of craft entrepreneurship knowledge from waste materials in the form of flat shapes and spaces in student groups. This can be seen from the average value of comparison between pre-cycle, cycle I, and cycle II there is an increase. There was a response of students in the application of local content curriculum in the effort of forming character education towards entrepreneurial knowledge of class XI students of SMA Negeri 7 Denpasar in the academic year 2019/2020.